Cubics, Rectangles and Parallelograms.

Geometry Level 3

The graph of the cubic function above has has real roots at x = p , x = p x = p, x = -p and x = 0 x = 0 and the lines B C BC and A D AD are tangent to the curve at B B and D D respectively.

If the two tangent points and two non-zero -intercepts are joined together to rectangle A B C D ABCD and the area A A of parallelogram B F E D BFED is A = a b A = \dfrac{a}{b} , where a a and b b are coprime positive integers, find a + b a + b .


The answer is 11.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Nov 29, 2018

m ( x ) = x ( x p ) ( x + p ) = x 3 p 2 x d m d x x = x 0 = 3 x 0 2 p 2 = x 0 ( x 0 p ) ( x 0 + p ) x 0 p m(x) = x(x - p)(x + p) = x^3 - p^2x \implies \dfrac{dm}{dx}|_{x = x_{0}} = 3x_{0}^2 - p^2 = \dfrac{x_{0}(x_{0} - p)(x_{0} + p)}{x_{0} - p} \implies
3 x 0 2 p 2 = x 0 + p x 0 2 x 0 2 p x 0 p 2 = 0 x 0 = p , p 2 3x_{0}^2 - p^2 = x_{0} + px_{0} \implies 2x_{0}^2 - px_{0} - p^2 = 0 \implies x_{0} = p, -\dfrac{p}{2}

x 0 p x 0 = p 2 B : ( p 2 , 3 p 3 8 ) x_{0} \neq p \implies x_{0} = -\dfrac{p}{2} \implies B:(-\dfrac{p}{2}, \dfrac{3p^3}{8}) and D : ( p 2 , 3 p 3 8 ) D:(\dfrac{p}{2}, -\dfrac{3p^3}{8}) .

A C = B D = 2 p = p 4 16 + 9 p 4 64 = 16 + 9 p 4 p 4 = 16 3 p = 2 3 4 . AC = BD = 2p = \dfrac{p}{4}\sqrt{16 + 9p^4} \implies 64 = 16 + 9p^4 \implies p^4 = \dfrac{16}{3} \implies p = \dfrac{2}{\sqrt[4]{3}}.

To obtain the area of parallelogram B F E D BFED you can:

(1) Find the area of the region bounded by the line the curve m ( x ) = x 3 4 3 m(x) = x^3 - \dfrac{4}{\sqrt{3}} and the line y = 1 3 x 2 27 4 y = -\dfrac{1}{\sqrt{3}}x - \dfrac{2}{\sqrt[4]{27}} then double the result.

Or

(2) Use slopes and distances to find the area.

Using (1):

A ( 2 3 4 , 0 ) , D ( 1 3 4 , 3 4 ) A(-\dfrac{2}{\sqrt[4]{3}}, 0), D(\dfrac{1}{\sqrt[4]{3}}, -\sqrt[4]{3})

m A D = 1 3 y = 1 3 x 2 27 4 = n ( x ) \implies m_{AD} = -\dfrac{1}{\sqrt{3}} \implies y = -\dfrac{1}{\sqrt{3}}x - \dfrac{2}{\sqrt[4]{27}} = n(x)

and,

m ( x ) = x 3 4 3 x m(x) = x^3 - \dfrac{4}{\sqrt{3}}x

A 1 = A 2 = 1 3 4 1 3 4 m ( x ) n ( x ) d x = \implies A_{1} = A_{2} = \displaystyle\int_{-\frac{1}{\sqrt[4]{3}}}^{\frac{1}{\sqrt[4]{3}}} m(x) - n(x) dx =

1 3 4 1 3 4 ( x 3 3 x + 2 3 3 4 ) d x = x 4 4 3 2 x 2 + 2 3 3 4 x 1 3 4 1 3 4 = 4 3 \displaystyle\int_{-\frac{1}{\sqrt[4]{3}}}^{\frac{1}{\sqrt[4]{3}}} (x^3 - \sqrt{3}x + \dfrac{2}{3^{\frac{3}{4}}}) dx =\dfrac{x^4}{4} - \dfrac{\sqrt{3}}{2}x^2 + \dfrac{2}{3^{\frac{3}{4}}}x|_{-\frac{1}{\sqrt[4]{3}}}^{\frac{1}{\sqrt[4]{3}}} = \dfrac{4}{3}

A B F E D = 8 3 = a b a + b = 11 . \implies A_{BFED} = \dfrac{8}{3} = \dfrac{a}{b} \implies a + b =\boxed{11}.

Using (2) :

m A D = m B C = 1 3 m_{AD} = m_{BC} = -\dfrac{1}{\sqrt{3}} .

For A D : y = 1 3 x 2 27 4 \overline{AD}: y = -\dfrac{1}{\sqrt{3}}x - \dfrac{2}{\sqrt[4]{27}}

For \perp line F G FG that passes thru F : ( 1 3 4 , 1 27 4 ) F: (\dfrac{1}{\sqrt[4]{3}}, \dfrac{1}{\sqrt[4]{27}}) :

m = 3 y = 3 x 2 27 4 3 x 2 27 4 = 1 3 x 2 27 4 x = 0 y = 2 27 4 m_{\perp} = \sqrt{3} \implies y = \sqrt{3}x - \dfrac{2}{\sqrt[4]{27}} \implies \sqrt{3}x - \dfrac{2}{\sqrt[4]{27}} = -\dfrac{1}{\sqrt{3}}x - \dfrac{2}{\sqrt[4]{27}} \implies x = 0 \implies y = -\dfrac{2}{\sqrt[4]{27}}

G F = 2 27 4 \implies \overline{GF} = \dfrac{2}{\sqrt[4]{27}} and E D = B F = 4 27 4 ED = BF = \dfrac{4}{\sqrt[4]{27}} \implies

A B F E D = 2 3 1 4 4 3 3 4 = 8 3 = a b a + b = 11 A_{BFED} = \dfrac{2}{3^{\frac{1}{4}}} * \dfrac{4}{3^{\frac{3}{4}}} = \dfrac{8}{3} = \dfrac{a}{b} \implies a + b = \boxed{11} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...